Research of numerical methods of the decision of systems the differential equations - Шибицький, В. П.; Бороденко, І. А. (Proceedings of National Aviation University (archive), 2003)
The technique of research of accuracy and convergence differed methods of the decision of the differential equations is offered. Methods Runge-Kutt, Adams i BDF are examined by means of the formula of return differentiation